Information Provision For Design Of The Range Of Industrial Clothing (Eurasian Journal of Engineering and Technology, 2024)
The article deals with the development of information and methodological support for the decision-making process in the formation of the assortment, industrial clothing. The structure of the information retrieval process at the initial stages of design is proposed, which provides a search for options for graphic solutions for special clothing based on the identification of optimal zones of contamination and wear of clothing in accordance with real operating conditions. A database of graphic diagrams of various design and technological solutions has been developed, which allow expanding the functional modules of automated systems. The use of a graphic base for displaying a collection of industrial clothing in computer-aided design significantly reduces design development time and reduces the number of errors caused by the human factor.